2019
DOI: 10.3390/nu11020284
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Product Intake and Cardiometabolic Diseases in Northern Sweden: A 33-Year Prospective Cohort Study

Abstract: Dairy products are important constituents of most diets, and their association with adverse health outcomes remains a focus. We characterized dairy food intake and examined associations with the incidence of type 2 diabetes (T2D), myocardial infarction (MI) or stroke among 108,065 Swedish men and women. Hazard ratios (HRs) and 95% CIs were estimated using the multivariable Cox proportional hazards models in a population characterized by high milk tolerance. During a mean follow-up of 14.2 years, 11,641 first-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…From the Malmö Diet and Cancer cohort 16 , the results on total dairy and butter were included in the data synthesis, and from the EPIC-NL cohort 52 , the results on total dairy, low-fat dairy and high-fat dairy were included in the data synthesis due to the different exposures than in the EPIC cohort 21 . Thus, 30 studies were included in the qualitative data synthesis [12][13][14][15][16][17][18][19][20][21][22][23][36][37][38][39][40][41][42][43][44][45]47,48,[50][51][52][53]55,56 (20 studies for CHD 12,13,[16][17][18][19][20][21][22][37][38][39][40]45,48,[50]<...>…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the Malmö Diet and Cancer cohort 16 , the results on total dairy and butter were included in the data synthesis, and from the EPIC-NL cohort 52 , the results on total dairy, low-fat dairy and high-fat dairy were included in the data synthesis due to the different exposures than in the EPIC cohort 21 . Thus, 30 studies were included in the qualitative data synthesis [12][13][14][15][16][17][18][19][20][21][22][23][36][37][38][39][40][41][42][43][44][45]47,48,[50][51][52][53]55,56 (20 studies for CHD 12,13,[16][17][18][19][20][21][22][37][38][39][40]45,48,[50]<...>…”
Section: Resultsmentioning
confidence: 99%
“…No studies on peripheral artery disease were identified. Table 1 shows the characteristics of the 20 studies on CHD 12,13,[16][17][18][19][20][21][22][37][38][39][40]45,48,[50][51][52][53]56 . Among the 20 studies, 5 presented gender-specific results 17,20,21,50,53 , 3 comprised only men 13,45,56 and 3 comprised only women 12,18,40 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review suggested that bioactive components associated with dairy lipids, especially high fat products, may be beneficial for cardio-metabolic health [27]. In a previous study in the same population, we found that the source of dairy fat, e.g., non-fermented or fermented milk, determined whether a high intake increased or decreased the risk for type 2 diabetes and myocardial infarction [28]. However, generally effect sizes were small.…”
Section: Discussionmentioning
confidence: 95%